Legal Analysis of the Use of Artificial Intelligence (AI) In Medical Services in Indonesia - Bayqunie; Beri Virando; Devand Adyllon; Teguh Alyansyah; Tiarsen Buaton; Triagus Suswantoro (Lembaga Bale Literasi, 2026)
The development of Artificial Intelligence (AI) technology in healthcare has brought significant transformation to the medical service system in Indonesia. The use of AI in diagnosis, medical record analysis, telemedicine, and clinical decision-making improves the efficiency and accuracy of healthcare services. However, the application of AI also raises legal issues concerning patient data protection, the liability of medical personnel, and legal certainty in the event of AI-based diagnostic errors. This study uses a normative juridical research method with statutory and conceptual approaches. The results show that Indonesia does not yet have specific regulations on AI in medical services; therefore, its regulation remains scattered across Law Number 17 of 2023 concerning Health, Law Number 27 of 2022 concerning Personal Data Protection, and general provisions on civil and criminal liability. Legal liability for AI-based diagnostic errors remains attached to medical personnel and healthcare facilities insofar as there is negligence or a violation of professional standards.